Inhibition of copper corrosion in cooling seawater under flowing conditions by novel pyrophosphate. Issue 79 (28th August 2015) - Deyab, M. A.; Essehli, R.; El Bali, B.
<x xml:space="preserve">Abstract</x> The inhibition of copper corrosion in cooling seawater by novel pyrophosphate molecule SrNiP2O7 (SNP) was investigated under flowing conditions using mass-loss and electrochemical methods.